Drawings : The Eighty-first Exhibition by Artists of Chicago and Vicinity. - The Art Institute of Chicago (Chicago : The Art Institute of Chicago, 1985)
Ahrendt, Mary ; Alam, Shafiqul ; Altman, Edith ; Anderson, Craig ; Aubin, Barbara ; Barron, Nicholas A. ; Bartman, Lori ; Benson, Guy ; Berger, Fred ; Berkowitz, Susan Graf ; Blades, Barbara ; Bramson, Phyllis ; etc.
Drawings : The Eighty-first Exhibition by Artists of Chicago and Vicinity, The Art Institute of Chicago, Chicago, May 4 through June 16, 1985
boek